Perubahan Nasib Tokoh Utama dalam Cerpen Nikosia Karya Saadi Youssef (Analisis Semiotika Naratif A.J Greimas) - Ramadhan, Gia; Rohanda, Rohanda (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2024)
This research analyzes the changes in the main character’s  fate in the short story "Nicosia" by Saadi Youssef through the review of actant scheme and functional structure. It uses a qualitative paradigm with the Algirdas Julien Greimas (A.J. Greimas) narrative semiotics analysis approach. The formal object in this research is A.J. Greimas's semiotics, and the material object is the short story "Nicosia" already published on the website nizwa.com. The results and discussion show that the main character experiences a significant change in fate. The results and discussion show that the main character experiences a significant change in fate. Starting from the initial situation as someone with an uncertain life fate and troubled by anxiety, it ends with the main character's self-situation full of peace and tranquility. Several phenomena in the story are explained in the transformation that begins from the initial situation to result in the final situation. The placement of the main character as the subject, other supporting characters who act as helpers, and several things received by the main character can form a functional structure of the story that is limited to the isotop of space and time.